Model kurikulum progresif untuk pelatihan seni tari di Sekolah Tari Jugala - Keiza Mufarihana Gunadi; Heni Komalasari; Tatang Taryana (Universitas Pendidikan Indonesia, 2026)
As a non-formal institution, Sekolah Tari Jugala strives to maintain technical quality and philosophical values through a well-planned educational system. This study examines the implementation of a progressive curriculum at the Sekolah Tari Jugala as a strategic effort to preserve the authenticity of Jaipongan dance in the digital era. Using a qualitative descriptive method, data were gathered through participatory observation, in-depth interviews with managers and instructors, and documentation reviews. Data validity was ensured through source and method triangulation. The findings reveal that Sekolah Tari Jugala implements a tiered curriculum divided into three levels: Basic, Intermediate, and Advanced. Each level features specific repertoires, ranging from foundational movements to complex choreographies. The pedagogical approach focuses on face-to-face direct demonstrations and intensive physical drills, intentionally avoiding digital standardization to safeguard anatomical precision. Objective evaluations are held every four months, and students perform without stage costumes to allow for a meticulous assessment of torso alignment and leg stances. This systematic curricular structure effectively transforms traditional apprenticeship patterns into professional arts education. The consistency of conventional teaching methods, combined with rigorous mental conditioning, successfully produces dancers who possess not only artistic technicality but also strong mental resilience and cultural integrity amid modern societal changes.